Analisa Kerusakan Bantalan Pada Boiler Feedwater Pump - Soewono, Arka Dwinanda; Gunawan, Ezra Raditya; Darmawan, Marten (Cylinder : Jurnal Ilmiah Teknik Mesin, 2023)
The sliding bearing is an essential component in a centrifugal pump to withstand the loads and forces during the operation of the pump. Damage to the plain bearing component can decrease pump performance and cause further damage to other components. This research aims to analyze the damage that occurs to the bearing used in a boiler feedwater pump and determine the cause of the damage. The analysis was carried out by observing the forms of damage to the Babbitt layer on the bearing, identifying potential failures using the Failure Modes and Effect Analysis (FMEA) method, and establishing the root cause of the failure using the fishbone diagram. The analysis results show that the leading cause of damage to the bearing for the boiler feedwater pump is the bulk loss of the babbitt layer on the bearings.